The Climate Change in Türkiye: Evidence From A Structural Break Analysis (Third Sector Social Economic Review, 2026)
Since the second half of the 20th century, scientific evidence has firmly established climate change as an irreversible and serious global issue, leading to a steady increase in the number of studies addressing the topic. Temperature and precipitation are two primary indicators of climate change. This study investigates the presence of climate change in Türkiye’s NUTS-2 regions by examining long-term trends in these two variables. Data covering the period from 1950 to 2021 were obtained from the station-based records of the Turkish State Meteorological Service. The datasets were aggregated by NUTS-2 regions, and the Bai-Perron multiple structural break analysis was applied to identify significant shifts in temperature and precipitation patterns. The analysis detected structural breakpoints in average temperature across 25 out of 26 regions, with the exception of the TRA1 region (which includes Erzurum, Erzincan, and Bayburt provinces). These breakpoints primarily occurred during the 1990s and early 2000s. Across all regions, temperatures exhibited varying degrees of increase. The most significant temperature rise was observed in the TRB2 region (Van, Muş, Bitlis, and Hakkari), while the smallest increase occurred in the TR81 region (Zonguldak, Karabük, and Bartın). No structural breakpoints were identified in precipitation levels, suggesting that the pronounced changes in temperature have not yet been mirrored in precipitation patterns. However, when precipitation trends were analyzed relative to the years in which temperature breakpoints occurred, notable regional variations in precipitation amounts were observed. The effects of urbanization and industrialization on temperature change were also examined. The analysis revealed a statistically significant relationship between temperature change and urbanization, but no significant relationship with industrialization.
Keywords: Climate Change